A prospective multicentric analysis of patient data and functional tests of standard knee prosthesis compared to individualized knee prosthesis implantation (NexGen CR vs. ConforMIS iTotal CR). Issue 4 (27th April 2017) - Dirks, Alena; Bergmann, Martin; Mai, Sabine; Müller, David; Siebert, Werner
Aims and Objectives: : Knee prosthesis have traditionally been developed using average knee morphologies. However, patient-specific knee implants are now available, which are designed on the basis of an individual patient anatomy with preoperative CT scan. The Aim of this study was a comprehensive comparison of patient reports and blinded functional tests between patients who received a conventional implant (OTS, Zimmer NexGen CR Flex) and patients with a patient-specific implant (CIM, ConforMIS iTotal). Materials and Methods: : 121 patients with either a ConforMIS iTotal CR prosthesis (ConforMIS, Bedford USA, 60 patients) or a NexGen CR Flex prosthesis (Zimmer, Winterthur Switzerland, 61 patients) were prospectively recorded. Both patient group reveal no significant differences in BMI or age. However, patients in ConforMIS group were examined on an average of two months earlier than control group. The follow-up examinations were blinded and the collected data consist of the Knee Society Score (KSS) as well as functional tests consisting of an 8 m "walk" (WALK), a "Timed-Up-and-Go" (TUG) and the "Timed Up and Down Stairs" Test (TUDS). The "aggregated locomotor function (ALF) score" was then calculated based on the addition of the average times of the three function tests (ALF = WALK + TUG + TUDS). A 2-sample t-test was used to compare the functional tests between the CIM and OTS prosthesis groups. Results: : The analysis of functional tests showed no significant difference between patients of both cohorts. Patients which received a ConforMIS prosthesis moved as quickly as patients with a conventional prosthesis (p> 0.05 each). In addition, the ALF values showed no significant difference between the two groups (21.2 s vs. 21.7 s, p = 0.67). Furthermore, also the KSS scores did not differ in the two cohorts. Conclusion: : The results of this blinded follow-up study demonstrates, that patients with individualized knee prosthesis had no benefit in functional activities of daily life (WALK, TUG and TUDS) in comparison to patients with conventional knee endoprosthesia. Additionally, this study revealed no evidence of improved patient satisfaction, pain relief or fulfillment of expectations as measured by the KSS.